CONSTRUÇÃO E VALIDAÇÃO DA ESCALA DE ANSIEDADE NO TRABALHO (EAT-35) - Franzim Neto, Luciano (2014)
Anxiety is a concept studied since antiquity been widely researched in many branches of science. Anxiety can be understood as a warning sign, an emotional state that sometimes becomes annoying, being experienced by all humans. One way of measuring anxiety is through valid and accurate scales. Therefore, the aim of this study was to construct and validate a scale to assess anxiety in the workplace. Based on three dimensions of anxiety contained in the literature, was built at Work Anxiety Scale (EAT-35). Data were collected from the responses of 220 employees of the State of São Paulo, with a mean age of 34.27 (SD = 9.83) and most were female ( 84.5 por cento ) and higher education ( 64,5 por cento). Descriptive statistics, factor analysis and Cronbachs alpha were calculated . The results revealed a model of three dimensions of anxiety and the dimensions obtained adequate factor loadings and reliability coefficients. With the results produced by the analyzes of this study it can be concluded that the Anxiety Scale at Work (EAT-35) can be used as a tool to assess anxiety at work. New research conducting the application of confirmatory factor analyzes are given in order to confirm the results obtained by exploratory factor analysis during validation of EAT-35.